Neodymium magnets migrated into an internal supravesical hernia: a rare case of foreign body ingestion in children - Michiaki Ikegami; Yuichiro Miyaki; Takashi Hamano; Yurina Taira; Toshiaki Takahashi (Surgical Case Reports, 2023)
Abstract Background Foreign body (FB) ingestion is a common event in children. The management of the ingested FB depends on the location, type, number, size of the FBs, patient age, and symptoms. Although most FBs pass spontaneously through the gastrointestinal tract without causing serious injuries, the ingestion of multiple high-powered magnetic pieces, especially neodymium magnets (NMs) increases the risks of morbidity and mortality. Supravesical hernia (SH) is rarely occurs in children, and few studies have reported SH in pediatric patients. We report an extremely rare case of ingested NMs that migrated into an internal SH in a pediatric patient. Case presentation A 3-year-old boy who had accidentally swallowed two NMs 3 days ago presented with vomiting and lower abdominal pain. X-ray imaging and computed tomography (CT) suspected the presence of a 1.0-cm radiopaque FB located in the terminal ileum dorsal side of the bladder. Although his abdominal pain was gradually getting better after oral feeding, repeat abdominal X-ray imaging showed that the FB was in a stagnant in position. Therefore, surgical intervention was planned to remove the FB 1 week after his admission. Under general anesthesia, laparoscopic and fluoroscopic examinations were performed and the cecum was found adhered to the retroperitoneum between the right medial umbilical fold and the right wall of the urinary bladder. The FB was presumed to be located at the tip of the incarcerated cecum in the retroperitoneal space. Peritoneum incision was started near the medial inguinal fossa, and the Retzius space was opened in a manner similar to the transabdominal pre-peritoneal approach for inguinal hernia repair. Consequently, the patient was diagnosed with internal SH with FB migration. The incarcerated cecum was pulled out, which revealed intestinal wall perforation. The FB remained in the retroperitoneal space in the pelvic cavity. The FB was easily removed using intestinal forceps and identified as combined two NMs. The postoperative course was good, and the patient was discharged on postoperative day 5. Conclusions We experienced an extremely rare case of a pediatric patient who swallowed multiple NMs that migrated into an internal SH, and the laparoscopic minimally invasive removal was successful.